Pengaruh Asesmen Portofolio Disertai Pemberian Costructive Feedback Terhadap Motivasi Belajar Mahasiswa Biologi FTIK IAIN Kerinci - Juita, Dewi; . M, Yusmaridi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Research was triggered by the problem that encountered by researchers in the form of the learning motivation of students was low if the learning only used a discussion method in the lecture process. The purpose of this research was to determine the effect of the use of portfolio assessment accompanied by giving constructive feedback to learning motivation of students in scientific writing course. The research design that used was one group pre-test and post-test design. The sample in the research was the first semester of the B class in the Biology department, FTIK, IAIN Kerinci with the total numbers of students was 32 students. The instruments that used were learning motivation questionnaires of students that described from five indicators. Data from learning motivation results were analyzed through <N-Gain> to determine the improvement for each indicator of learning motivation. The results of this research are indicators of perseverance, interest, and independence which have a high improvement while indicators of tenacity and achievement can classified into the moderate category.